The Culture-bound Counsellor as an Unintentional Racist - Pedersen, Paul (Canadian Journal of Counselling and Psychotherapy, 2007)
Racism has been discredited as a scientific and biological term but highly visible racism in schools, universities, and social institutions demonstrate that racism remains an important political and psychological concept. Historically, racism has been given as an ideological, political, social and economic justification by one group to exploit others. This exploitation is not always done intentionally and many unintentional racists believe themselves to be fair. It is suggested in this article that we tend to underestimate the extent of personal and institutional racism by neglecting "unintentional racism" and by presuming that scientific objectivity will protect us from being racist.